1994
DOI: 10.1111/j.1524-4725.1994.tb02626.x
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Metastasis as First Sign of an Undifferentiated Carcinoma of the Lung

Abstract: Metastasis from internal neoplasms should be considered among other differential diagnoses in the evaluation of gingival tumors. In the present case, onset of oral lesion preceded detection of the primary lung tumor. Complete screening of the patient should therefore follow a diagnosis of gingival neoplasm of unknown origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…4 This case also highlights the importance of biopsy procedures to unravel the diagnosis of an apparent unpretentious case. Other authors also reported on oral cavity metastatic masses as a primary sign of a primary malignancy, as examples, Peris et al, 22 in 1994 diagnosed a gingival mass as the first evidence of a primary lung undifferentiated carcinoma; Llannes et al, 23 reported 2 cases of oral neoplasms that represented the first manifestation of hepatocellular carcinoma, similar to case 7; Patel et al 24 diagnosed a gingival mass as the first sign of a renal cell carcinoma and Park et al 25 have biopsied a gingival mass representative of an undifferentiated sarcomatoid carcinoma of the lung.…”
Section: Discussionmentioning
confidence: 95%
“…4 This case also highlights the importance of biopsy procedures to unravel the diagnosis of an apparent unpretentious case. Other authors also reported on oral cavity metastatic masses as a primary sign of a primary malignancy, as examples, Peris et al, 22 in 1994 diagnosed a gingival mass as the first evidence of a primary lung undifferentiated carcinoma; Llannes et al, 23 reported 2 cases of oral neoplasms that represented the first manifestation of hepatocellular carcinoma, similar to case 7; Patel et al 24 diagnosed a gingival mass as the first sign of a renal cell carcinoma and Park et al 25 have biopsied a gingival mass representative of an undifferentiated sarcomatoid carcinoma of the lung.…”
Section: Discussionmentioning
confidence: 95%
“…From 1964 to 2013, 28 cases of gingival metastasis from the primary lung carcinoma were detected according to English literature. There were 9 adenocarcinoma 1,7-14 (AC), 1 poorly differentiated adenocarcinoma 15 (pdAC), 3 squamous cell carcinoma [16][17][18] (SC), 2 small cell carcinoma 17,19 (SCC), 1 poorly differentiated squamous cell carcinoma 20 (pdSC), 2 large cell carcinoma 14,21 (LCC), 7 undifferentiated carcinoma 17,[22][23][24][25][26][27] (UDC), 1 leiomyosarcoma 18 (LS), 1 malignant fibrous histiocytoma 28 (MFH) and 1 epithelial cell carcinoma 29 (ECC) in all of these cases. Maxillary (14 cases) and mandibular (14 cases) gingiva were affected equally according to review of the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of metastatic tumors for which the primary tumor is unknown, we advocate performing a Pet-scan if the results of the Body-Scan are negative. The treatment will depend on many factors; however in cases of metastasis to soft tissue, complete excision is advisable regardless of the degree of dissemination (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). If it involves the bone and is the only location where it is seated, surgical resection is advised if possible, but if the extension study reveals evidence of the spread of the primary tumor or that the metastasis cannot be resected, palliative treatment is recommended.…”
Section: Discussionmentioning
confidence: 99%